Simultaneous Cranioplasty and Ventriculoperitoneal Shunt Placement After Decompressive Craniectomy in Children: A Single-Center Experience - Duygu Dolen Burak; Mustafa Selim Şahin; Cafer Ikbal Gülsever; Duran Sahin; Tugrul Cem Unal; Ilyas Dolas; Pulat Akin Sabanci; Yavuz Aras; Aydın Aydoseli; Altay Sencer (Journal of Clinical Medicine, 2026)
Background: The optimal sequencing of cranioplasty (CP) and ventriculoperitoneal shunt (VPS) placement after decompressive craniectomy (DC) remains uncertain, particularly in pediatric patients. This study aimed to describe our pediatric experience and provide an exploratory comparison of simultaneous and staged procedures. Methods: We retrospectively reviewed the medical records of 12 pediatric patients who developed hydrocephalus after DC at a single tertiary center between 2015 and 2023. Six patients underwent simultaneous CP and VPS placement, while six underwent staged VPS placement followed by CP. Demographic and clinical characteristics, surgical timing, postoperative complications, and neurological outcomes were compared. Given the small sample size, analyses were exploratory and primarily descriptive. Results: Postoperative complications occurred in two patients in each group (33.3%), including one wound infection and one shunt dysfunction requiring revision. No intracranial hemorrhage or deep shunt infection occurred in either group. The complication rate did not differ between the groups (p = 1.000). The median final Glasgow Outcome Scale score was 2.5 (range, 2–3) in the simultaneous group and 3.0 (range, 1–5) in the staged group (p = 0.457). Neurological outcomes likely reflected the severity of the underlying brain injury; however, the small sample size precluded adjustment for prognostic factors. Conclusion: In this small retrospective pediatric cohort, simultaneous CP and VPS placement was technically feasible, but postoperative complications occurred in one-third of patients. No significant differences were observed between the simultaneous and staged groups; however, these findings should not be interpreted as evidence of equivalence because of the limited sample size and non-randomized design. Surgical strategy should be individualized, and larger multicenter pediatric studies are needed.